Specific stress test design and performance profiling of high-level athletes in French boxing - Guerrero, M.; Gargagli, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: French boxing remains insufficiently explored regarding physical and physiological performance with studies highlighting performance in boxing, but not specifically in French boxing and under ecological conditions [1]. Other studies analysed boxing punches during three rounds of three minutes each, but French boxing is characterised by punches and kicks and rounds of two minutes. [2][3]. A complementary study has assessed physiological boxing performance in ecological conditions by designing a boxing test using a punching bag with an imposed stroke rate similar to competition [4]. Therefore, the aim of this study was twofold: (i) to establish a discipline-specific reference stress test and (ii) to collect data from this protocol on punching bag and in the ring in order to quantify the internal and external training load of top-level athletes. METHODS: Thirteen athletes from the French boxing national training centre took part in the study. The experimental protocol consisted of a maximal effort exercise on a punching bag designed to assess individual physiological performance. The following day a one-on-one confrontation in the ring during three rounds of two minutes each or five rounds of two minutes each was carried out, depending on each athlete competition format (assault or combat). During the two exercises, various physiological data were collected, including blood lactate and glucose levels, and heart rate. Gas exchange was measured during the punching bag task. The number and accuracy of punches and kicks were also recorded RESULTS: This study showed that the athletes reached their maximum physiological capacity in the punching bag task (184±10bpm; 52,6±7ml/min/kg) , suggesting that this exercise is a relevant discipline-specific reference stress test. A random slope model showed that the type of exercise had no significant effect on the metabolic response of each athlete, unlike the rounds (p